Issues in interpreting the in vivo activity of Aurora-A inhibitors - Shagisultanova, Elena (Expert Opin Ther Targets, 2014)
INTRODUCTION: Based on its role as a mitotic regulatory kinase, overexpressed and associated with aneuploidy in cancer, small molecule inhibitors have been developed for Aurora-A (AURKA) kinase. In preclinical and clinical assessments, these agents have shown efficacy in inducing stable disease or therapeutic response. In optimizing the use of Aurora-A inhibitors, it is critical to have robust capacity to measure the kinase activity of Aurora-A in tumors. AREAS COVERED: we provide an overview of molecular mechanisms of mitotic and non-mitotic activation of Aurora-A kinase, and interaction of Aurora-A with its regulatory partners. Typically, Aurora-A activity is measured by use of phospho-antibodies targeting an auto-phosphorylated T288 epitope. However, recent studies have identified alternative means of Aurora-A activation control, including allosteric regulation by partners, phosphorylation on alternative activating residues (S51, S98), dephosphorylation on inhibitory sites (S342), and T288 phosphorylation by alternative kinases such as Pak enzymes. Additional work has shown that the relative abundance of Aurora-A partners can affect the activity of Aurora-A inhibitors, and that Aurora-A activation also occurs in interphase cells. EXPERT OPINION: Taken together, this work suggests the need for comprehensive analysis of Aurora-A activity and expression of Aurora-A partners in order to stratify patients for likely therapeutic response.